(untitled) (CIPEEX, 2026)
The language used by the Judiciary has a direct impact on the effectiveness of communication between the State and the citizen. The excessive use of legal terms, traditionally considered complex, has long been revealed as one of the main obstacles to the understanding of judicial decisions and the active participation of the population in judicial processes. Attentive to this demand, the Brazilian Judiciary has, in recent years, experienced initiatives to simplify the language used within its scope, especially in judicial decisions. In this context, this research aims to map institutional initiatives aimed at simplifying legal language, evaluating their practical effects. The present study, developed through bibliographical and documentary research, aims to analyze the simple language movement within the scope of Law, presenting the National Simple Language Pact in Brazil and CNJ Recommendation nº 144/2023, as well as some initiatives of good communicative practices existing in the Judiciary, all aligned with the constitutional principles of due legal process, publicity and efficiency.